Reasonability and Conscientious Objection in Medicine: A Reply to Marsh and an Elaboration of the Reason-Giving Requirement - Card, Robert F. (Bioethics, 2014)
In this paper I defend the Reasonability View: the position that medical professionals seeking a conscientious exemption must state reasons in support of their objection and allow those reasons to be subject to evaluation. Recently, this view has been criticized by Jason Marsh as proposing a standard that is either too difficult to meet or too easy to satisfy. First, I defend the Reasonability View from this proposed dilemma. Then, I develop this view by presenting and explaining some of the central criteria it uses to assess whether a conscientious objection is proper grounds for extending an exemption to a medical practitioner.